PENGARUH MODEL PEMBELAJARAN HYPNOTEACHING DALAM MENINGKATKAN HASIL BELAJAR SEJARAH DI SMA N 1 WATOPUTE - Ridayat, Ridayat; Elsin, Waode; Yusran, Yusran; Udu, Azura; Melinda, Eka; Faliadin, Faliadin (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
This study aims to determine the effectiveness of the hypnoteaching method in history lessons in improving student learning outcomes at Watopute 1 State Senior High School. The method used is a quantitative research method. This type of research is a quasi-experimental study with a Nonequivalent Control Group Design. The sampling technique used a nonrandom assignment technique, resulting in 25 students in Grade XI IPA 1 as the experimental class and 28 students in Grade XI IPA 2 as the control class. Data analysis techniques used were t-test analysis, gain score testing, and regression testing. The results of the study indicate that the application of the hypnoteaching method in history lessons has an effect on improving student learning outcomes at Watopute 1 State Senior High School. This is evidenced by the t-test results showing a significance value less than 0.05 (p = 0.035 <0.05). The gain score in the experimental class was 0.41, categorized as moderate effectiveness, while the control class obtained a gain score of 0.17, categorized as low effectiveness. The significant impact of the application of the hypnoteaching method in history lessons on improving student learning outcomes at SMA N 1 Watopute was 41.5%. ABSTRAKPenelitian ini bertujuan untuk mengetahui seberapa efektif pengaruh pembelajaran  dengan penerapan metode hipnoteaching melalui pada mata pelajaran sejarah dalam meningkatkan hasil belajar peserta didik di SMA  N 1 Watopute. Metode yang digunakan adalah metode penelitian kuantitatif. Jenis penelitian eksperimen kuasi dengan desain Nonequivalent Control Group Design. Teknik pengambilan sampel menggunakan teknik nonrandom assignment sehingga didapat XI IPA 1 sebagai kelas eksperimen sebanyak 25 peserta didik dan XI IPA 2 sebagai kelas kontrol sebanyak 28 peserta didik. Teknik Analisis data yang digunakan adalah analisis uji t-test, uji gain score dan uji regresi. Hasil penelitian menunjukkan bahwa: penerapan metode hipnoteaching pada mata pelajaran sejarah berpengaruh dalam meningkatkan hasil belajar peserta didik di SMA  N 1 Watopute. Hal ini dibuktikan dari hasil uji-t menunjukkan nilai signifikansi lebih kecil dari 0,05 (p= 0,035 < 0,05). Hasil gain score pada kelas eksperimen sebesar  0,41 masuk kategori efektivitas sedang, sedangkan kelas kontrol memperoleh gain score 0, 17 dalam kategori efektivitas rendah. Besarnya pengaruh penerapan metode hipnoteaching pada mata pelajaran sejarah dalam meningkatkan hasil belajar peserta didik di SMA N 1 Watopute sebesar 41,5%.